Demographic differences in letters of recommendation for economics Ph.D. students - Beverly J. Hirtle; Anna Kovner (Federal Reserve Bank of New York, 2024)
We analyze 6,400 letters of recommendation for more than 2,200 economics and finance Ph.D. graduates from 2018 to 2021. Letter text varies significantly by field of interest, with significantly less positive and shorter letters for Macroeconomics and Finance candidates. Letters for female and Black or Hispanic job candidates are weaker in some dimensions, while letters for Asian candidates are notably less positive overall. We introduce a new measure of letter quality capturing candidates that are recommended to "top" departments. Female, Asian, and Black or Hispanic candidates are all less likely to be recommended to top academic departments, even after controlling for other letter characteristics. Finally, we examine early career outcomes and find that letter characteristics, especially a "top" recommendation have meaningful effects on initial job placements and journal publications.
Keywords: A11; A23; J15; J16; 330; recommendation letters; gender in economics; race and ethnicity in economics; research institutions; professional labor markets